Pelatihan Pembuatan Menu Sate Lilit Ikan Tenggiri sebagai Alternatif DASHAT (Dapur Sehat Atasi Stunting) di Kelurahan Krandon - Nurdian Susilowati; Salsabila Aurielle Febriane; Lina Adilah (Jurnal Bina Desa, 2024)
Real Work Lecture (KKN) activities with the theme of Stunting have implemented a Healthy Kitchen Overcoming Stunting or DASHAT work program to overcome the problem of stunting in Krandon Village. This healthy kitchen program is implemented by providing cooking demonstration training to PKK mothers so that they provide nutritious and balanced menu cooking innovations for their children, especially for toddlers aged 12 to 24 months. The purpose of implementing the Healthy Kitchen by KKN students is to provide information and awareness to mothers who have children under 2 years of age to provide healthy and nutritionally balanced food for their children, with the hope that children's development can be maximized and avoid stunting. In this community service activity, it is carried out by holding demonstrations and training in food processing, namely satay lilit tenggiri fish with balanced nutrition for children under 2 years of age, and the menu chosen remains economical so that the knowledge shared can be applied at home.